RISK FACTORS FOR MYCOPLASMA GALLISEPTICUM SEROPREVALENCE IN CHICKENS - M. Z. Islam; S. Ahmed; Md F. Hossain; A. Mahmood; A. Ahad; S. Chowdhury; J. P. Christensen (Journal of Animal and Plant Sciences, 2015)
Avian Mycoplasmosis is a chronic respiratory disease which causes very low mortality but it decreases egg production and causes carcass condemnation. A cross sectional study was conducted from September 2010 to October 2012 to identify the potential risk factors for Mycoplasma gallisepticum (Mg) seroprevalence in commercial chicken production in Chittagong area, Bangladesh. A total of 5589 serum samples were collected from one hundred chicken flocks of different production systems (commercial layer, broiler and layer breeder). Antibody against Mycoplasma gallisepticum was determined by commercial indirect Enzyme Linked Immunosorbent Assay (ELISA) kit. A multivariable logistic regression model was designed to evaluate the risk factors for Mg seroprevalence. The ELISA test results demonstrated that 32% of the birds were seropositive to Mg antibodies in the study area. A multivariable logistic regression model identified a strong effect of ‘age’ on the Mg antibody level where birds of more than 53 weeks of age showed the greatest risk of being positive for Mg (OR 419.27, 95% CI 294.67-596.54, P<0.0001) compared to birds less than 16 weeks of age. Moreover, monsoon season (OR 2.962, 95% CI 2.24-3.92, P<0.0001), male birds (OR 1.192, 95% CI 1.03-1.38, P=0.0196) and Commercial layer type of production system (OR 2.641, 95% CI 2.17-3.22, P<0.0001) were factors found to be associated the risk of attracting Mg in chickens.
Keywords: Mycoplasmosis; Seroprevalence; ELISA; Antibody